Delimitation of the upstream region of NFKBIA gene associated with HTLV-1-associated myelopathy/tropical spastic paraparesis using candidate Tag-SNPs in Peruvian HTLV-1 infected individuals - Posadas A.E. (2019)
This study was supported by the FONDECYT -Peru and Directorate General for Development Cooperation of the Belgian Government through the framework agreement with the Institute of Tropical Medicine of Antwerp and through the Flemish Interuniversity Council (VLIR).